Direct red decolorization and ligninolytic enzymes production by improved strains of Pleurotus using basidiospore derived monokaryons - Srivastava, A. K.; Vishwakarma, S. K.; Pandey, V. K.; Singh, M. P. (Cellular and Molecular Biology, 2014)
In the present investigation the efficiency of three species of Pleurotus and their improved dikaryons (heterokaryons) was assessed for decolorization of direct red and production of lignin peroxidase (LiP), manganese peroxidase (MnP) and laccase enzymes. All the species of Pleurotus i.e. P. flabellatus, P. ostreatus, and P. citrinopileatus decolorized the dye Direct Red well. However, Pfo 6X9 and Poc 9X6 decolorized the dye more effectively than three species of Pleurotus. The improved dikaryons also showed higher ligninolytic activity than the parental species. Poc 9X6 showed higher LiP (76.27U), MnP (623.24U) and laccase activity (594.80U). In the present work different pH, age and concentration of inoculum and effect of surfactant i.e. sodium dodecyl sulphate (SDS) and Tween-80 were analyzed in order to determine the optimum ones to decolorize maximum concentration of dye. 5 ml of 10 days old culture on pH 5.5 and 0.1% Tween-80 supported maximum decolorization of direct red dye.